Acceptability and Complications of Postpartum Intrauterine Device Insertion in Tertiary Care Hospital in Eastern Nepal - Sunuwar Subedi, Shanti; Yadav, M; Yadav, D (Nepal Medical College Journal, 2020)
The modern intrauterine contraceptive device (PPIUCD) is a safe, effective and long term reversible, coitus independent method of contraception with fewer side effects. The immediate postpartum insertion is considered to be an ideal time as patients need not have to return to the facility for the same. The aim of the study was to see the acceptance of PPIUCD and study its related complications. This is a hospital based prospective observational study done in a tertiary hospital at Eastern Nepal over a period of Six months from August 2019 to January 2020. All the women who delivered during the study period were counseled for family planning methods and those who opted for PPIUCD were enrolled. Data was validated and analyzed using SPSS version 17. Acceptance of PPIUCD in the study was only 6.3% despite the method being very effective, safe, long acting and reversible with fewer side effects. The main reason for declining the method being misbelief about the method and husband’s refusal. Forty percent of the acceptors were in the age group of 21-25 years and 33.6% of them were multigravida. Insertion was high in post placental vaginal delivery (61%) as compared to trans cesarean (28%). The main reason for removal was psychosocial aspects followed by pelvic pain and abnormal uterine bleeding. Few complications like UTI (4.4%), fever (4%) were noted during hospital stay and at three month follow up pelvic pain was the most common problem reported. Though the overall acceptance of PPIUCD is in rising trend but in this study it is very low. Awareness of the method, improving health education, active participation of the partner in the counseling process will definitely change the recent scenario. It should be incorporated in the government schemes like Safe Motherhood to cover the high unmet need of contraception in Nepal.